2005
DOI: 10.1207/s15327914nc5101_5
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Study: Potential Role of Vitamin D (Cholecalciferol) in Patients With PSA Relapse After Definitive Therapy

Abstract: When local treatments for prostate cancer have failed, and prostate-specific antigen (PSA) rises in the absence of symptoms, there is little consensus as to the best management strategy. Calcitriol has been shown to prolong the doubling time of PSA in this context, but near-toxic doses are required. We investigated the effect of the nutrient vitamin D (cholecalciferol), a biochemical precursor of calcitriol, on PSA levels and the rate of rise of PSA in these patients. Fifteen patients were given 2,000 IU (50 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0
3

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 11 publications
2
41
0
3
Order By: Relevance
“…The inclusion of PSA in the analyses did not affect the estimated hazard ratios when differentiation grade was included in the analyses (not illustrated). Woo et al (2005) observed in a pilot study that a high level of 1,25(OH) 2 D prolongs the doubling time of PSA, which is in line with our results. Unfortunately, in this study we have no repeated measurements of PSA, and hence we were not able to investigate the possible relationship between 25(OH)D levels and the doubling time of PSA.…”
Section: Discussionsupporting
confidence: 92%
“…The inclusion of PSA in the analyses did not affect the estimated hazard ratios when differentiation grade was included in the analyses (not illustrated). Woo et al (2005) observed in a pilot study that a high level of 1,25(OH) 2 D prolongs the doubling time of PSA, which is in line with our results. Unfortunately, in this study we have no repeated measurements of PSA, and hence we were not able to investigate the possible relationship between 25(OH)D levels and the doubling time of PSA.…”
Section: Discussionsupporting
confidence: 92%
“…Some investigations have followed the approach of administering very high doses of calcitriol intermittently, such as three times a week (Trump et al 2006) or once weekly (Beer et al 2003), when it apparently can still elicit anti-proliferative effects but cause only transient hypercalcemia and limited toxicity (Beer et al 2003, Trump et al 2006. The use of nutrient vitamin D (cholecalciferol), the biochemical precursor of calcitriol, has also been evaluated in a pilot clinical study, revealing a beneficial effect of prolongation of PSA doubling time (Woo et al 2005).…”
Section: Clinical Studies Of Calcitriol In Pcamentioning
confidence: 99%
“…294 Recently, Vieth and colleagues reported that when vitamin D (2000 IU daily) was administered to 15 prostate cancer patients in whom local therapy had failed (PSA measurable and rising), the PSA doubling time increased from 14.3 months to 25 months, decreasing at least slightly in 14 of the 15 subjects; 9 of the 15 patients experienced no rise in PSA, or a small decline, for months following initiation of vitamin D supplementation. 295 In addition, very recent epidemiology suggests that vitamin D status at the time of initial diagnosis may have a significant impact on cancer prognosis, suggesting that good vitamin D status during initial therapy may have a notable impact on the success of this therapy. [296][297][298] Thus, although the relevant evidence is still fragmentary, it seems prudent to ensure that patients maintain good vitamin D status with a daily dose of this vitamin that is of real physiological significance, perhaps 2000 to 4000 IU daily.…”
Section: Ensuring Good Micronutrient Statusmentioning
confidence: 99%